2016
DOI: 10.2147/ccid.s116548
|View full text |Cite
|
Sign up to set email alerts
|

Reactivating the extracellular matrix synthesis of sulfated glycosaminoglycans and proteoglycans to improve the human skin aspect and its mechanical properties

Abstract: BackgroundThe aim of this study was to demonstrate that a defined cosmetic composition is able to induce an increase in the production of sulfated glycosaminoglycans (sGAGs) and/or proteoglycans and finally to demonstrate that the composition, through its combined action of enzyme production and synthesis of macromolecules, modulates organization and skin surface aspect with a benefit in antiaging applications.Materials and methodsGene expression was studied by quantitative reverse transcription polymerase cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…If DCN acts as a niche component to maintain HFSC and the decrease in the number of HFSC is caused by age‐related changes in the niche, DCN expression may reduce with age. We performed immunohistochemistry against DCN and found that DCN was strongly expressed across the dermis, as shown in the previous study . We observed DCN signals at a higher magnification so that the strong DCN signal in the dermis did not impede close observation and quantification of DCN localization in the area around HFSC.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…If DCN acts as a niche component to maintain HFSC and the decrease in the number of HFSC is caused by age‐related changes in the niche, DCN expression may reduce with age. We performed immunohistochemistry against DCN and found that DCN was strongly expressed across the dermis, as shown in the previous study . We observed DCN signals at a higher magnification so that the strong DCN signal in the dermis did not impede close observation and quantification of DCN localization in the area around HFSC.…”
Section: Resultssupporting
confidence: 73%
“…We performed immunohistochemistry against DCN and found that DCN was strongly expressed across the dermis, as shown in the previous study. 25 We observed DCN signals at a higher magnification so that the strong DCN signal in the dermis did not impede close observation and quantification of DCN localization in the area around HFSC. It was shown that DCN was localized on the basement membrane alongside KRT15-positive HFSC in young subjects and the DCN signal as well as the KRT15 signal were remarkably reduced with age ( Fig.…”
Section: Age-related Decrease In Dcn Expression In the Bulge Regionmentioning
confidence: 84%
“… 121 Chajra and co-workers utilized a similar strategy for boosting sulfated GAG levels with a formulation containing GAG precursors and synthesis intermediaries, finding it increased sulfated GAG levels within cultured human skin fibroblasts and ex vivo human skin, while improving dermal structure of ex vivo skin samples and increasing skin smoothness in a cohort of female volunteers. 122 Jasmonic acid derivatives (JAD) have also been demonstrated to increase proteoglycan expression and modify GAG fine structure in skin, as well as potentiate KGF signaling. Consistent with these in vitro data, JAD treatment promotes re-epithelialization clinically within a suction-cup blister model of wound healing.…”
Section: Cosmetic Approaches For Anti-aging Gag/proteoglycan Modulationmentioning
confidence: 99%
“…The various anti-aging benefits of GAGs have contributed to their widespread inclusion in cosmetic and pharmaceutical products (50,51). GAGs, including hyaluronic acid, chondroitin sulfate, dermatan sulfate and keratan sulfate are abundant structural components of extracellular structures and regulate many biological processes, including cell growth, migration, differentiation, adhesion and lipid synthesis in the dermis and epidermis (1,(52)(53)(54)(55)(56). The contents of GAGs change during intrinsic and extrinsic aging (57)(58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of collagen synthesis/degradation is thus a pivotal target for anti-wrinkle agents. Glycosaminoglycans (GAGs) are highly charged polysaccharides that are an important structural component of the extracellular matrix (ECM) and are often used in cosmetic products (1)(2)(3). In a previous clinical trial, it was identified that a cream containing GAGs regulated wrinkles, skin elasticity, dermal density and skin tightening (4).…”
Section: Introductionmentioning
confidence: 99%